Circularly polarized reflection spectra of a photonic beetle and preparation of tunable circularly polarized light reflecting device consisting of conductive polymer/beetle exoskeleton - Hiromasa Goto; Katsuto Yamaguchi; Ryo Miyashita (Next Materials)
The surface structure of the exoskeleton of Anomala albopilosa as a photonic insect is visually examined, followed by the measurement of the circularly polarized laser reflection spectrum to assess the reflection of circularly polarized light from the surface. The elytron of Anomala albopilosa is coated with the conductive polymer polyaniline (PANI). The PANI layer alters the transmission of light through the doping-dedoping process. This light shutter function enables the tuning of circularly polarized light reflection from the elytron surface, providing a tunable circularly polarized light reflector. This composite represents a novel bio/synthetic polymer combination with tunable circularly polarized light reflection intensity.